A Prospective Study on Breathing Therapy’s Impact on Pain in Acute Abdominal Colic Patients - Mastuti, Siti; Susilowati, Yuli; Suwaryo, Putra Agina Widyaswara (Babali Publisher, 2023)
Introduction: This research addresses the dynamics of abdominal colic presentations in the Emergency Department (ED), focusing on respondents predominantly in their productive years. Among 67 patients seeking urgent care for abdominal colic, a majority were males, underscoring the significance of understanding the impact of this condition on individuals in their prime. Despite enduring prolonged and unbearable pain, a noteworthy finding is the delay in seeking medical attention, attributed to occupational commitments. The most prevalent occupations were in the private sector, with a substantial number engaged in entrepreneurial activities and civil service. Work-related responsibilities emerged as a primary deterrent to immediate medical care, revealing a complex interplay between professional obligations and personal health priorities. The study aimed to explore demographic patterns, uncover factors influencing the timing of seeking medical attention, and contribute insights to improve healthcare delivery for individuals with abdominal colic. Methods: Employing a prospective observational design, data were collected from 85 patients in the ED, integrating numeric pain scales and diaphragmatic breathing therapy. Results: Results indicated a significant reduction in pain scores post-therapy, particularly in the productive age group. In conclusion, the research highlights the unique challenges faced by individuals with abdominal colic, emphasizing the need for tailored interventions considering occupational constraints. The findings underscore the importance of timely medical attention and prompt interventions to enhance patient outcomes. Conclusion: This research provides valuable insights into the complexities surrounding abdominal colic management in the ED, serving as a foundation for further studies and targeted healthcare strategies.